Efficacy And Autodissemination Of Aedestech Mosquito Home System (Amhs) On Aedes Mosquitoes In Laboratory And Small-scale Field Study - Abdullah, Fatin Nabila (2024)
Ovitrap deployment stands as a viable strategy for Aedes mosquito control. This study evaluated the efficacy of an autodissemination ovitrap called AedesTech Mosquito Home System (AMHS), which incorporates pyriproxyfen. This study encompassed laboratory trials and a small-scale field study. The objective of the field study was to comprehensively assess the impact of AMHS on Aedes, non-target insects, and dengue infection rates in mosquitoes. Within the laboratory trials, these investigations unfolded across two species of mosquitoes: Aedes albopictus and Aedes aegypti. Three distinct facets were explored in the laboratory trials: the influence of an attractant on the oviposition, the effect of trap positioning on oviposition, and the selection of oviposition sites. The field study conducted in Asoka Apartment, Pulau Pinang, unfolded in three successive periods: baseline study, effectiveness study, and autodissemination study. Concurrently, the accuracy of the AedesTech Mobile App (ATA) was scrutinized. The laboratory results indicated the Mosquito Home Aqua (MHAQ) solution with attractant consistently attracted Ae. aegypti effectively (Welch's ANOVA, F(2,68.66)=5.22,p=0.01). However, its efficacy with Ae. albopictus was suboptimal compared to other treatments (Two-way ANOVA, F=0.16,df=2,p>0.05), highlighting the need for considering additional attractants. Notably, the placement of AMHS exhibited no discernible impact on its attractiveness for both mosquito species (T-test,p>0.05), underscoring the flexibility in trap deployment.